2018
DOI: 10.1016/j.molmet.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β receptor 1 regulates progenitors that promote browning of white fat

Abstract: ObjectiveBeige/brite adipose tissue displays morphological characteristics and beneficial metabolic traits of brown adipose tissue. Previously, we showed that TGF-β signaling regulates the browning of white adipose tissue. Here, we inquired whether TGF-β signals regulated presumptive beige progenitors in white fat and investigated the TGF-β regulated mechanisms involved in beige adipogenesis.MethodsWe deleted TGF-β receptor 1 (TβRI) in adipose tissue (TβRIAdKO mice) and, using flow-cytometry based assays, iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 64 publications
(100 reference statements)
1
24
1
Order By: Relevance
“…TGF-β's role in regulating apoptosis in normal and diseased cells is well known 63 . We have previously shown that TGF-β antagonism can protect mice from obesity and diabetes 60,64 . The findings here support a role for controlled TGF-β inhibition in combating β-cell apoptosis and restoring the β-cell mass in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β's role in regulating apoptosis in normal and diseased cells is well known 63 . We have previously shown that TGF-β antagonism can protect mice from obesity and diabetes 60,64 . The findings here support a role for controlled TGF-β inhibition in combating β-cell apoptosis and restoring the β-cell mass in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that progenitor autophagy inhibition similarly favors beigeing and also minimizes adipose tissue fibrogenic potential, even in mice fed an obesogenic diet. The TGF pathway is a key actor in fibrogenesis, and some TGFb family members have been reported to modulate the development of beige adipocytes [40,41], but it is still unclear how TGFb family members/receptor pathways govern this inverse relationship. There is clinical relevance in this question because acting on both AT fibrosis (an ultimate sign of dysfunction linked to insulin resistance) and AT browning (a favorable metabolic phenotype with positive effects on glucose utilization) would be expected to positively influence metabolic health when combined.…”
Section: Beyond a Primary Role Of Progenitor Autophagy Status In Fibrmentioning
confidence: 99%
“…The TGFβ pathway has emerged as a critical anti-adipogenic player through the Smad 2/3 activation (33)(34)(35). Deletion of TGFβ receptor 1 in mice has been shown to promote brown-like adipogenesis within white adipose tissue, thus supporting a model where TGFβ receptor signaling plays a role in regulating the pool of BAPs (36). The Smad2/3 pathway was found to be active during hiPSC-BAP differentiation, suggesting that bioactive TGFβ family members were secreted, which might lock differentiation (24).…”
Section: Critical Role Of the Tgfβ Pathway In Hipsc-ba Progenitor Difmentioning
confidence: 96%
“…Figure 1 illustrates the regulation of brown-like adipocyte generation from hPSCs by the retinoic acid and TGFβ pathways. Wankhade and colleagues proposed that negative regulation of PGE2/Cox-2 by TGFβ is involved in the recruitment of brown-like adipose progenitors (36). Interestingly, inhibition of the TGFβ pathway is not a prerequisite for adult adipose tissue-derived adipose progenitor differentiation.…”
Section: Critical Role Of the Tgfβ Pathway In Hipsc-ba Progenitor Difmentioning
confidence: 99%